Integrated Monitoring for the Rock Mass State During Large-Scale Subsoil Development - Bazaluk, Oleg; Rysbekov, Kanay; Nurpeisova, Marzhan; Lozynskyi, Vasyl; Kyrgizbayeva, Guldana; Turumbetov, Turar (Frontiers in Environmental Science, 2022)
The purpose of this paper is to develop a methodology for integrated monitoring for the rock mass state, which ensures the industrial and environmental safety of the Central Kazakhstan region. As a result of the research, a methodology for maintaining an integrated system of geodynamic monitoring has been developed. The results of predicting the physical-mechanical properties and stress-strain state of the rock mass are presented. Based on the data obtained, graphical-analytical dependences between the most important quantitative characteristics of the rock properties in the studied deposits are presented. The scientific novelty of the presented research is in determining the pattern of changes in the structural peculiarities and strength properties of rocks with the depth of their occurrence, which makes it possible to predict the stress-strain state of the rock mass. The authors propose a new method for creating a geodynamic test site. The geodynamic test site created in the fields of Central Kazakhstan is a reliable basis for the organization of long-term monitoring for the earth's surface deformation processes during large-scale development of the field, which improves the productivity and accuracy of observations. The results obtained can be used to im-prove the level of industrial safety at mines and minimize environmental risks caused by the subsoil development.